RECURRENCE RISK OF INFERIOR SURFACE LEUKOPLAKIA OF THE VOCAL CORDS: A RETROSPECTIVE STUDY - Rohit Kumar Jha; Sanjay Kumar (Student's Journal of Health Research, 2023)
Background: Vocal fold leukoplakia (VFL) remains a diagnostic and therapeutic challenge despite our knowledge of its etiopathogenetic factors and the development of laryngeal visualisation. This study sought to identify lesions on the inferior surface of the vocal folds as a recurrence risk factor. Methods: This was a retrospective study with two years of data collection. The study included 37 VFL patients, who were separated into nonrecurrent and recurrent categories. Each patient's clinicopathological characteristics and surgical procedures were scrutinised. Results: 15 (40.5%) of the 37 patients exhibited residual (3) or recurrent (12) VFL. 8 of 12 (66.7%) patients with recurrence and 6 of 22 (27.3%) patients without recurrence had inferior surface lesions of the vocal fold at the time of the initial operation (P =.036). Significantly more recurrences occurred in patients with inferior surface lesions. Other evaluated factors were not associated with recurrence. Conclusion: The presence of VFL lesions on the inferior surface is a significant recurrence risk factor.